The Deployment Life Study : methodological overview and baseline sample description - Tanielian, Terri L.; Karney, Benjamin R.; Chandra, Anita; Meadows, Sarah O. (Sarah Opal), 1978- (Rand Corporation, 2014)
In the past decade, U.S. military families have experienced extreme stress, as U.S. soldiers, sailors, airmen, and marines have experienced extended and repeated deployments. As a result, U.S. policymakers and Department of Defense leadership have placed an emphasis on family readiness for deployment and other military-related stressors. However, family readiness is not a well-understood construct. The Deployment Life Study was designed to provide a deeper understanding of family readiness and to address the sources of readiness among military families. It is a longitudinal study of military families over the course of a full deployment cycle--predeployment, during deployment, and postdeployment. Over the course of three years, the study will follow 2,724 families from each service and component, interviewing service members, their spouses, and one child between the ages of 11 and 17 in each family (if applicable) every four months. Baseline data are weighted to be representative of married service members who were eligible to deploy sometime between June 1, 2012, and December 31, 2012. This report describes the Deployment Life Study theoretical model; the content of the baseline assessment; the design and procedures associated with data collection, sampling and recruiting procedures; and the baseline sample of military families.